Cumulative cardiotoxic effect of bleomycin in experiment - Gozhenko, A.; Bestanchuk, O.; Kaschenko, O.; Narbutova, T. (Journal of Education, Health and Sport, 2021)
The aim of the study was to evaluate the cumulative toxic effect of bleomycin under experimental conditions Material and Methods. The study was conducted in the Research Institute of Transport Medicine during 2016-2021. The experimental model of the cardiotoxic effect of the bleomycin was performed using the medication "Bleocin" manufactured by Nippon Kayaku Co., Ltd. (Japan). According to the task, the study was performed on 10 mature rats of both sexes of the Wistar line with a body weight of 237 ± 20 g. Rats were housed in standard vivarium conditions of Odessa National Medical University. Animals were divided into 2 groups: experimental group (n = 5) and control (n = 5). Bleomycin animals of the experimental group were obtained intraperitoneally at a dose of 0.5 IU / kg on 1st and 8th days. Withdrawal of animals from the experiment was performed on the 5th, 14th and 28th day of the experiment, followed by morphological and morphometric examination. The material after weighing and morphometry was fixed with a neutral 10% formalin solution and poured into paraffin. Histological sections were stained with hematoxylin-eosin, MSB, Van Gizon. Performed light microscopy. After two weeks there was a decrease in myocardial weight by 7-10% from baseline, there were pronounced dystrophic changes in the myocardium. Repeated administration of bleomycin has a cumulative cardiotoxic effect leading to irreversible changes in the myocardium and endothelial dysfunction clinically manifested by heart attack, vascular pathology at significant cumulative doses of bleomycin. Morphofunctional changes of the right ventricle are prominent and considered to be pathognomic for bleomycin toxicity. Conclusions: 1. Bleomycin has a cumulative toxic effect on the myocardium of mammals 2. The severity of the cardiotoxic effect of bleomycin is proportional to the tissue concentration of the drug, which is proportional to the duration of exposure